Congenital granular cell epulis: A case series - Mustafa Okumuş; Adil Umut Zubarioğlu; Uğuray Payam Hacısalihoğlu (EL-Med-Pub, 2020)
Background: Congenital granular cell epulis (CGCE) is an extremely rare intraoral tumor of the newborn with a potential to disrupt feeding and produce respiratory distress. Case Series: We report two newborns presented with mass protruding off the mouth since birth. The mass was arising from alveolar ridge in both cases and dealt with surgical excision. Histopathology revealed it congenital granular cell epulis. Postoperative recovery and follow-up are uneventful. Conclusion: Congenital granular cell epulis is a benign lesion though not quite uncommon, may cause diagnostic challenges. Early excision and histopathology rule out malignant lesions.